Ultrasound Markers of Carotid Atherosclerosis and Cognition: The Northern Manhattan Study - Gardener, Hannah (Stroke, 2017)
BACKGROUND AND PURPOSE—: Ultrasound markers of carotid atherosclerosis may be related to cognitive status. We hypothesized that individuals with greater carotid intima–media thickness (cIMT) and carotid plaque burden would exhibit worse cognition. METHODS—: One thousand one hundred sixty-six stroke-free participants from the NOMAS (Northern Manhattan Study) underwent carotid ultrasound and neuropsychological examination. Among them, 826 underwent a second neuropsychological examination an average of 5 years later. cIMT and plaque were assessed by a standardized B-mode ultrasound imaging and reading protocol. We used multivariable linear regression to examine cIMT, carotid plaque presence, and carotid plaque area as correlates of domain-specific neuropsychological Z scores cross-sectionally and over time. We also investigated possible effect modification by APOE ε4 allele, age, and race/ethnicity. RESULTS—: Participants had a mean (SD) age of 70 (9) years and were 60% women, 66% Hispanic, 15% white, and 18% black. Those with greater cIMT exhibited worse episodic memory after adjustment for demographics and vascular risk factors (β=−0.60; P=0.04). APOE ε4 carriers with greater cIMT exhibited worse episodic memory (β=−1.31; P=0.04), semantic memory (β=−1.45; P=0.01), and processing speed (β=−1.21; P=0.03). Participants with greater cIMT at baseline did not exhibit significantly greater cognitive decline after adjustment. APOE ε4noncarriers with greater cIMT exhibited greater declines in executive function (β=−0.98; P=0.06). Carotid plaque burden was not significantly associated with cognition at baseline or over time. CONCLUSIONS—: Subclinical carotid atherosclerosis was associated with worse cognition among those at higher risk for Alzheimer disease. Interventions targeting early stages of atherosclerosis may modify cognitive aging.